2010
DOI: 10.1101/gr.102970.109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping and assembly of structural variant breakpoints in the mouse genome

Abstract: Structural variation (SV) is a rich source of genetic diversity in mammals, but due to the challenges associated with mapping SV in complex genomes, basic questions regarding their genomic distribution and mechanistic origins remain unanswered. We have developed an algorithm (HYDRA) to localize SV breakpoints by paired-end mapping, and a general approach for the genome-wide assembly and interpretation of breakpoint sequences. We applied these methods to two inbred mouse strains: C57BL/6J and DBA/2J. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
247
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(260 citation statements)
references
References 65 publications
11
247
2
Order By: Relevance
“…Except for small insertions, SMASH consistently detected breakpoints with allelic frequencies >1.7%. To see if SMASH produces results comparable to other SV algorithms, we compared its breakpoint detection to HYDRA (Quinlan et al 2010;Malhotra et al 2013) on a set of simulated breakpoints (Supplemental Material; Supplemental Table T3). Overall, SMASH breakpoint detection rates were similar to HYDRA, with SMASH more accurately resolving breakpoint coordinates and HYDRA more consistently detecting short insertions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for small insertions, SMASH consistently detected breakpoints with allelic frequencies >1.7%. To see if SMASH produces results comparable to other SV algorithms, we compared its breakpoint detection to HYDRA (Quinlan et al 2010;Malhotra et al 2013) on a set of simulated breakpoints (Supplemental Material; Supplemental Table T3). Overall, SMASH breakpoint detection rates were similar to HYDRA, with SMASH more accurately resolving breakpoint coordinates and HYDRA more consistently detecting short insertions.…”
Section: Resultsmentioning
confidence: 99%
“…Structural variation methods, such as GASV (Sindi et al 2009), SegSeq (Chiang et al 2009), DELLY (Rausch et al 2012b), HYDRA (Quinlan et al 2010), AGE (Abyzov and Gerstein 2011), and others (Lee et al 2008; for review, see Snyder et al 2010;Alkan et al 2011), generally utilize (1) read-pair (RP) discordance, (2) increase or reduction in sequence coverage, (3) split reads that span breakpoints, and (4) exact assembly of breakpoint sequences. These tools were primarily designed for variant detection from a single data set, such as a normal genome, and are suited for cataloguing structural polymorphisms in the human population (Kidd et al 2008(Kidd et al , 2010Mills et al 2011).…”
mentioning
confidence: 99%
“…The likelihood of local hopping of the SB transposon is increased on the chromosome where the transposon concatamer is located (62); thus, all insertions on chromosome 4, the site of the T2/Onc2 donor concatamer, were removed from the dataset before subsequent analysis, unless indicated otherwise. Sfi1 is listed as a singlecopy gene in the reference mouse genome; however, it is estimated that the mouse genome has 20-30 copies of Sfi1 (63). Insertions in multiple different Sfi1 loci are erroneously annotated to a single Sfi1 gene located on chromosome 11; thus, we removed Sfi1 from our lists of CIS genes, because this is a known artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Structural variation is widespread in mammalian genomes 34,35 and is an important cause of disease. 36 Genome-wide association studies identified single-nucleotide polymorphisms in several genes, such as GRIA4, KCNQ5, RDH5, LAMA2, BMP2, SIX6, PRSS56, GJD2, RASGRF1, ZC3H11B, and WNT7B, as risk factors for refractive error including myopia.…”
Section: Discussionmentioning
confidence: 99%